The potential of lasmiditan in migraine - Mecklenburg, Jasper (Ther Adv Neurol Disord, 2020)
Lasmiditan, a highly selective 5-hydroxytryptamine receptor 1F (5-HT(1F)) agonist, is the first drug in its class and is lacking triptan-like vasoactive properties. The US Food and Drug Administration (FDA) has recently approved lasmiditan for the acute treatment of migraine in adults based on positive results of two pivotal phase III trials, which showed a significant difference to placebo in the proportion of patients achieving total migraine freedom within 2 h. More patients with lasmiditan achieved headache freedom and, in addition, freedom from the most bothersome symptom, that is, photophobia, than with placebo. Treatment-related side effects seem to be related to the rapid penetration of the drug into the brain and include dizziness, paresthesia and drowsiness, mostly of mild to moderate intensity. Interim results from an ongoing long-term phase III trial suggest a decrease in the frequency of adverse events after multiple lasmiditan use. Lasmiditan is a promising acute anti-migraine therapy, in particular for patients with cardiovascular risk factors, contraindications, or unwanted side effects to triptans.